(3GdfbhO h GdHfhc Hjf GdfXQjI h GdJWHjbs - (3CfS(B, (3GdHcQjs; (3hdjO UGaj(B, s ((3YeGf(B:s (3OGQ GdeSJbHd ddfTQ hGdJhRjY(B,s, 2009)
(3GdfbhO h GdfXe GdfbOjI h GdGUOGQ GdfbOj, Shb GdfbO, GdWdH h GdYQV Ydi GdfbhO, GdHfc GdeQcRj h GdHfhc GdJLGQjI h GdHfhc GdGSdGejI, GdeDSSGJ GdeGdjI GdeJNUUI, Ndb GdfbhO, GdhOGFY , GdSjGSGJ GdfbOjI h GdJVNe , eY hLhO CSFdI h JeGQjf aj fgGjI cd aUds
(3edGMb U(B.213 (3HHdjhZQGajG(B: (3U(B.217s
Keywords: (3GdHfhcs; (3GdHfhc GdGSdGejIs; (3GdHfhc GdJLGQjIs; (3GdfbhOs